Revolusi penilaian dalam sistem pemantauan pelajar (i-RAS) (Revolution on assessment for student monitoring system (i-RAS) / Mohd Samsudin Abdul Hamid ...[et al.] - Abdul Hamid, Mohd Samsudin; Mohamad Nor, Md Rasul; Abdullah, Nor Hafizah Hanis; Hassan, Siti Hafizan; Tukiar, Mohd Azuan; Abd Karim, Nurulzatushima; Hassan, Ahmad Syauqi; Azizan, Fairus Azwan; Ismail, Shafienaz; Fauzi, Mohd Azrizal; Mohamed Noor, Suhailah (Universiti Teknologi MARA, 2020)
Effectiveness of a programme is measured through the achievement of Course Outcomes and Programme Outcomes (COPO). However, problems occur when number of courses and lecturers increased and yet the process of collecting and analysing all the data were done manually. Therefore, systematic and effective tools are required to tackle these problems. Furthermore, all engineering programme offered under the faculty must implement the Outcome Based Education (OBE) system as a curriculum approach for the purpose of accreditation from Boards of Engineers Malaysia (BEM) through Engineering Accreditation Council (EAC) for bachelor degree and Engineering Technician Accreditation Council (ETAC) for diploma. Therefore, an effective system called i-RAS (Revolution on Assessment for Student Monitoring System) has been developed to overcome the improper analysis of COPO. This system has been implemented for bachelor degree at Faculty of Civil Engineering UiTM Penang Branch. The advantages of this system are (i) paperless because all the data were uploaded in the faculty website, (ii) automatic data analysis and (iii) the storage system is safer than before. As a result, the Bachelor Degree of Civil Engineering (Infrastructure) has succesfully attained 5 (FIVE) years accreditation. Seeing this successful story, the Dean of Civil Engineering Faculty has 44 44 standardized the implementation of this system throughout all campuses offering Diploma of Civil Engineering such as in Pasir Gudang Campus (Johor), Jengka Campus (Pahang), Permatang Pauh Campus (Penang) and Samarahan Campus (Sarawak).This system also has boost satisfaction among the lecturers up to 97%, time saving up to 78% and development system cost saving up to RM29,700 (100%). This system also helped the faculty to attain full accreditation for all the programs offered by this faculty.